Our Experience in Combined Carotid Endarterectomy andCoronary Bypass Surgery: Postoperative Early Results in 480Patients - Tekin, Esra Ertürk; Uysal, Ayhan; Vezir, Özden (My University, 2021)
Objective: Due to the diffuse nature of atherosclerosis, cerebrovascular, and coronary arterydisease may present simultaneously. A proportion of the patients undergoing cardiac surgery are atan increased risk for carotid artery disease (CAD) related neurological events. The ideal operationstrategy is still controversial in patients with concomitant carotid artery stenosis (CAS) undergoingcoronary artery bypass grafting (CABG). In this study, we aimed to evaluate the outcomes ofisolated CABG versus combined surgery (CEA+CABG) in patients with CAD and to identify thepossible correlation between CAD and stroke. Materials and Methods: Between January 2017 and April 2019, medical files of a total of 480patients who underwent carotid artery Doppler ultrasonography before CABG were retrospectivelyanalyzed. Demographic and clinical data of the patients and carotid artery status as assessed byDoppler USG were recorded. Neurological complications were evaluated during the hospital stay. Results: Of the patients, 312 were males and 168 were females with a mean age of 62±10.4(range: 44 to 78) years. A statistically significantly higher number of patients with severe CAD hada preoperative history of cerebrovascular accident (P=0.048), advanced age (P=0.002), prior CEA(P=0.576), and peripheral artery disease (P=0.048). Of 36 patients with severe CAD, 21 underwentcombined surgery. None of the patients treated with CEA+CABG had neurological events. Theneurological in-hospital mortality and morbidity was 3.2% in 459 patients with isolated CABG. Conclusion: Combined surgery can yield the most favorable outcomes in patients with severeCAD or symptomatic CAD accompanied by unstable angina, left main coronary artery disease, andmulti-vessel disease.
Keywords: Genel ve Dahili Tıp; Kalp ve Kalp Damar Sistemi; Cerrahi